Reduce the Anxiety of the Elderly Through Individual Counseling the Tazkiyatun Nafs Approach - Nidya Juwita Roza (Jurnal Masyarakat Religius dan Berwawasan, 2022)
This research is motivated by the high anxiety experienced by the elderly. This has a negative impact on theirlives. To suppress anxiety, the treatment that is deemed appropriate is by way of tazkiyatun nafs. In this way, humanscan rid themselves of dirty qualities so as to produce good behavior. The purpose of this service activity is to reduce theanxiety experienced by the elderly so that the elderly can live an effective daily life and obtain happiness in life in thisworld and in the hereafter. The research findings show that the anxiety experienced by the elderly generally occurs inthe physical and cognitive aspects. The results of data analysis showed that before being given treatment in the form ofindividual counseling with the tazkiyatun nafs approach, the average level of anxiety in the elderly was still high. Whengiven treatment in the intervention conditions, the trend towards the anxiety level of the elderly decreased on average.This proves that individual counseling with the tazkiyatun nafs approach has an effect on reducing the anxiety of theelderly